The importance of Madʻū (Invited) In Preaching - Farida Yousuf; Kalsoom Paracha (jihat-ul-islam, 2021)
In present era one of the most important department is preaching. Islam allows to spread its message to enlighten human beings and this process is continued from its early period till today. Yet it can be said that the desired results are still far away and one of the reasons of this failure is the way this message is being spread. Basically, preaching of enjoining good and forbidding wrong is the responsibility of governments and states. Yet due to the neglecting attitude of governments and states, different groups are preaching these teachings relying on their own resources and manpower. There are three basic elements of preaching i.e, Dʻawat, Dāʻī and Madʻū. The present research focuses on Madʻū because the desired results cannot be attained by neglecting the psychology of Madʻū. That is why there is a need to revise not only the curriculum but also the methodology of preaching (by these groups). And these changes should be made on the basis of mental ability, social background, psychology and financial status of Madʻū. This article examines the division and rights of Madʻū so the objectives of preaching and enlightenment can be achieved as it should be.